Cardiac autonomic control and complexity during sleep are preserved after chronic sleep restriction in healthy subjects. Issue 7 (13th April 2017) - Tobaldini, Eleonora; Covassin, Naima; Calvin, Andrew; Singh, Prachi; Bukartyk, Jan; Wang, Shiang; Montano, Nicola; Somers, Virend K.
Abstract: Acute sleep deprivation (SD) alters cardiovascular autonomic control (CAC) and is associated with an increased risk of cardiovascular disorders. However, the effects of partial SD on CAC are unclear. Thus, we aimed to investigate the effects of partial SD on CAC during sleep. We randomized seventeen healthy subjects to a restriction group (RES, n = 8, subjects slept two‐thirds of normal sleep time based on individual habitual sleep duration for 8 days and 8 nights) or a Control group (CON, n = 9, subjects were allowed to sleep their usual sleep time). Attended polysomnographic (PSG) studies were performed every night; a subset of them was selected for the analysis at baseline (day 3‐D3), the first night after sleep restriction (day 5‐D5), at the end of sleep restriction period (day 11‐D11), and at the end of recovery phase (day 14‐D14). We extracted electrocardiogram (ECG) and respiration from the PSG and divided into wakefulness (W), nonrapid eye movements (REM) sleep (N2 and N3) and REM sleep. CAC was evaluated by means of linear spectral analysis, nonlinear symbolic analysis and complexity indexes. In both RES and CON groups, sympathetic modulation decreased and parasympathetic modulation increased during N2 and N3 compared to W and REM at D3, D5, D11, D14. Complexity analysis revealed a reduction in complexity during REM compared to NREM sleep in both DEP and CON. After 8 days of moderate SD, cardiac autonomic dynamics, characterized by decreased sympathetic, and increased parasympathetic modulation, and higher cardiac complexity during NREM sleep, compared to W and REM, are preserved. Abstract : Acute sleep deprivation (SD) alters cardiovascular autonomic control (CAC) and is associated with an increased risk of cardiovascular disorders. We randomized seventeen healthy subjects to a restriction group (RES, n = 8) or a Control group (CON, n = 9) and we analyzed CAC during sleep. After 8 days of moderate SD, cardiac autonomic dynamics, characterized by decreased sympathetic, and increased parasympathetic modulation, and higher cardiac complexity during NREM sleep, compared to W and REM, are preserved.